On the Versatility of Accessory Mineral Geochronology in Addressing the Age and Provenance of Geological Material - Clarke, Anthony Joseph Ian (Curtin University, 2024)
Zircon U–Pb is the principal radiometric dating technique, yet associated biases may hamper interpretations of geological phenomena. This thesis presents isotopic (U–Pb, Lu–Hf, Sm–Nd) and chemical data for apatite and rutile to demonstrate how accessory minerals can complement conventional zircon geochronology. Holistic insights into processes occurring over geological time can be obtained through a multi-mineral and isotopic system approach to geochronology.